Potential role for microbial ureolysis in the rapid formation of carbonate tufa mounds. Issue 1 (2nd August 2021) - Medina Ferrer, Fernando; Rosen, Michael R.; Feyhl‐Buska, Jayme; Russell, Virginia V.; Sønderholm, Fredrik; Loyd, Sean; Shapiro, Russell; Stamps, Blake W.; Petryshyn, Victoria; Demirel‐Floyd, Cansu; Bailey, Jake V.; Johnson, Hope A.; et al.
Abstract: Modern carbonate tufa towers in the alkaline (~pH 9.5) Big Soda Lake (BSL), Nevada, exhibit rapid precipitation rates (exceeding 3 cm/year) and host diverse microbial communities. Geochemical indicators reveal that carbonate precipitation is, in part, promoted by the mixing of calcium‐rich groundwater and carbonate‐rich lake water, such that a microbial role for carbonate precipitation is unknown. Here, we characterize the BSL microbial communities and evaluate their potential effects on carbonate precipitation that may influence fast carbonate precipitation rates of the active tufa mounds of BSL. Small subunit rRNA gene surveys indicate a diverse microbial community living endolithically, in interior voids, and on tufa surfaces. Metagenomic DNA sequencing shows that genes associated with metabolisms that are capable of increasing carbonate saturation (e.g., photosynthesis, ureolysis, and bicarbonate transport) are abundant. Enzyme activity assays revealed that urease and carbonic anhydrase, two microbial enzymes that promote carbonate precipitation, are active in situ in BSL tufa biofilms, and urease also increased calcium carbonate precipitation rates in laboratory incubation analyses. We propose that, although BSL tufas form partially as a result of water mixing, tufa‐inhabiting microbiota promote rapid carbonate authigenesis via ureolysis, and potentially via bicarbonate dehydration and CO2 outgassing by carbonic anhydrase. Microbially induced calcium carbonate precipitation in BSL tufas may generate signatures preserved in the carbonate microfabric, such as stromatolitic layers, which could serve as models for developing potential biosignatures on Earth and elsewhere.